Finite Precision Rational Arithmetic: Slash Number Systems - Matula, David W.; Kornerup, Peter (DAIMI Report Series, 1983)
Fraction number systems described by fixed-slash and floating slash formats are specified. The structure of arithmetic over such systems is prescribed by the rounding obtained from ’’best rational approximation’’. Multi-tiered precision hierarchies of both fixed-slash and floating-slash type are proposed and analyzed with regards to their support of both exact rational and approximative real computation.